Kontribusi Islam Terhadap Kemajuan Ilmu Pengetahuan dan Imperialisme Berat Terhadap Dunia Islam - Naila Fazila; Nurzena (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Islamic civilization is one of the civilizations that made a significant contribution to the development of world science, especially during the golden age of Islam. This study aims to analyze the contribution of Islamic civilization in the development of various scientific disciplines and examine the impact of Western imperialism on the decline of the Islamic world. This study uses a qualitative method with a library research approach. Primary data were obtained from major works discussing the history and development of Islamic civilization, while secondary data were obtained from books, scientific journal articles, proceedings, and relevant previous research results, including the works of Philip K. Hitti, Seyyed Hossein Nasr, Marshall G. S. Hodgson, Jonathan M. Bloom, Sheila S. Blair, as well as various academic publications on the history of Islamic science and Western colonialism. Data were analyzed using content analysis techniques through a process of identification, classification, and interpretation of information according to the research focus. The results show that Islamic civilization contributed significantly to the fields of medicine, mathematics, astronomy, philosophy, and technology, and played a role as a bridge for the transmission of science to the Western world. In addition, Western imperialism had an impact on weakening the political, economic, social and scientific traditions of Islam, which influenced the decline of Islamic civilization in the modern era.